EVALUATION OF MOBILE-BASED E-SAMSAT SYSTEM SERVICES IN BANJARMASIN CITY WITH METHOD TECHNOLOGY ACCEPTANCE MODEL AND IMPORTANCE PERFORMANCE ANALYSIS - Andry Fajar Zulkarnain; Eka Setya Wijaya; Triana Rifkah (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2022)
The E-Samsat application uses the Technology Acceptance Model (TAM) method to find out how the attitudes of users, the response of the Banjarmasin community in paying motor vehicle taxes with the E-Samsat application or manually and using the Importance Performance Analysis (IPA) method to provide an assessment of service and use of E-Samsat. using the Cartesian quadrant. This study uses a questionnaire to obtain data. Questionnaires were distributed to the people of Banjarmasin City and people who paid motor vehicle taxes at the Banjarmasin II Samsat Office. From the results of the analysis based on the TAM method with user attitudes. The Importance Performance Analysis (IPA) method lies in which quadrant the statement items have been answered by the respondent.